HNA-1d: a new human neutrophil antigen located on Fcγ receptor IIIb associated with neonatal immune neutropenia. - Reil, Angelika; Sachs, Ulrich J; Tania Siahanidou; Flesch, Brigitte K; Bux, Juergen (Transfusion, 2013)
BACKGROUND: Neonatal immune neutropenia (NIN) is a rare, but potentially life-threatening, disorder caused by maternal alloantibodies recognizing paternal neutrophil antigens on fetal cells. Alloantibodies directed against the human neutrophil alloantigen system (HNA)-1 located on Fcγ receptor IIIb (FcγRIIIb) are most frequently implicated in NIN. In this report, we describe two cases of NIN with alloantibodies against FcγRIIIb, which did not match one of the known HNA-1a, -1b, or -1c specificities, but define a new antigen, HNA-1d. STUDY DESIGN AND METHODS: Neutrophil-reactive antibodies were detected by agglutination, microscopic immunofluorescence, and monoclonal antibody (MoAb)-specific immobilization of neutrophil antigens (MAIGA) assay. For epitope mapping of FcγRIIIb-reactive antibodies, recombinant chimeric variants of FcγRIIIb were used in the MAIGA assay. Genotyping of FCGR3B was performed by allele-specific polymerase chain reaction. RESULTS: Both mothers were typed FCGR3B*01+, *02-, *03+. Antibody screening revealed the presence of alloantibodies reactive with FcγRIIIb encoded by FCGR3B*02, but not with FcγRIIIb encoded by FCGR3B*03. MAIGA with recombinant, partly chimeric FcγRIIIb variants demonstrated that the antigen recognized by maternal antibodies is characterized by two amino acids, Ala78 and Asp82. Among the FCGR3B alleles, the sequence Ala78–-Asn82 is exclusively encoded by FCGR3B *02. CONCLUSION: A previously unrecognized second antigen, HNA-1d, is present on FcγRIIIb encoded by FCGR3B*02. This antigen is characterized by the sequence Ala78–-Asn82. It appears that only individuals carrying the HNA-1c phenotype can form anti-HNA-1d alloantibodies. The HNA-1 system now consists of four antigens encoded by three alleles.
Keywords: Adult; Epitope Mapping; Female; Genotype; GPI-Linked Proteins; Humans; IgG; Infant; Isoantibodies; Isoantigens; Male; Neutropenia; Neutrophils; Newborn; Receptors